Application Of The Profile Matching Method For A Decision Support System In Selecting The Quality Of Fresh Fruit Marks (FFB) Of Oil Palm Worth Harvesting - Miranti Harahap, Putri; Dur, Sajaratud; Fathoni, Muhammad (Publisher Cv. Inara, 2025)
Oil palm has an important role for the country's economy and is one of the commodity crops for Indonesian plantations. The oil content in palm oil has benefits for everyday life such as cooking oil, processed food, cosmetics and so on. Selection of quality fresh fruit bunches (FFB) for oil palm suitable for harvest requires a method to determine which fresh fruit bunches (FFB) are very suitable. One way to do this is by using the profile matching method. The profile matching method is a method of making decisions by assuming that there is an ideal variable level. The results of the study concluded, among others: the decision support system used to assist in selecting the quality of fresh fruit bunches (FFB) of oil palm worth harvesting. The application of the profile matching method can make decisions in selecting the quality of fresh fruit bunches worth harvesting based on ranking for the 30 samples used. TBS20 with a value of 4.9 is ranked first and TBS16 with a value of 3 is ranked last.